2010
DOI: 10.1177/193229681000400318
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Glucose Monitoring System in a Rural Intensive Care Unit: A Pilot Study Evaluating Accuracy and Acceptance

Abstract: The CGMS is well tolerated by ICU patients but, at present, is not sufficiently accurate to be used for therapeutic decisions in the acute setting, particularly in patients with diabetic ketoacidosis. There is a need to find resolution to the technical issues regarding electrode "wetting" and calibration if CGMS use in the ICU setting is to provide an effective means of diabetes care and management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
36
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(37 citation statements)
references
References 29 publications
1
36
0
Order By: Relevance
“…During the present study, the proportion of sensor glucose values within 20% of reference glucose was 88% with the enhanced protocol, compared with reported values between 63% and 75% [14][15][16] other than for Brunner et al, 17 who reported a higher percentage of 92%. Most intensive care unit studies evaluated Medtronic (Northridge, CA) sensors, 14,[16][17][18] and only one study evaluated Navigator.…”
Section: Discussionmentioning
confidence: 49%
See 1 more Smart Citation
“…During the present study, the proportion of sensor glucose values within 20% of reference glucose was 88% with the enhanced protocol, compared with reported values between 63% and 75% [14][15][16] other than for Brunner et al, 17 who reported a higher percentage of 92%. Most intensive care unit studies evaluated Medtronic (Northridge, CA) sensors, 14,[16][17][18] and only one study evaluated Navigator.…”
Section: Discussionmentioning
confidence: 49%
“…Most intensive care unit studies evaluated Medtronic (Northridge, CA) sensors, 14,[16][17][18] and only one study evaluated Navigator. 19 Further improvements in accuracy may be achievable through the intravenous sampling route eliminating or significantly reducing the lag time of 6-15 min reported with subcutaneous sensors.…”
Section: Discussionmentioning
confidence: 99%
“…However, CGM did not affect the degree of hyperglycemia when compared to intermittent BG testing, which could possibly be explained by having already achieved tight glycemic control in the intermittent BG testing group. 30 In other reports, Jacobs et al showed that their subcutaneous CGM was not sufficiently accurate outside of the euglycemic spectrum 31 and Brunner et al did not appreciate a difference in the control of glycemic variability in their retrospective study of 63 patients. 32 The clinical accuracy of different continuous monitors in various clinical settings is still being explored.…”
Section: Discussionmentioning
confidence: 99%
“…BMI, body mass index; EF, ejection fraction; WBC, white blood cell; HDL-C, high density lipoprotein-cholesterol; LDL-C, low density lipoprotein-cholesterol Data are reported as the mean ± SD or n (%). BMI, body mass index; EF, ejection fraction; WBC, white blood cell; HDL-C, high density lipoprotein-cholesterol; LDL-C, low density lipoprotein-cholesterol other studies argued that CGMS glucose values are not sufficiently accurate and reliable to be used for therapeutic decisions [30][31][32]. Currently, clinical experience with CGMS in CCUs is limited, particularly for STEMI patients undergoing p-PCI.…”
Section: Discussionmentioning
confidence: 99%